2018
DOI: 10.1128/mbio.00758-18
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Pathway of Human T-Cell Leukemia Virus Type 1 Gag Punctum Biogenesis Provides New Insights into Enveloped Virus Assembly

Abstract: This report describes the results of experiments examining the pathway by which the human retroviral Gag protein is recruited to sites along the inner leaflet of the plasma membrane where Gag punctum biogenesis occurs. In particular, clever and sensitive experimental methods were devised to image in living cells fluorescently labeled Gag protein derivatives from human T-cell leukemia virus type 1 (HTLV-1) and human immunodeficiency virus type 1 (HIV-1) at the plasma membrane. The photoconvertible fluorescent p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 62 publications
1
10
0
Order By: Relevance
“…Analogous to our observation, a recent study found that when the MA domain of HIV-1 Gag was replaced with the N-terminal PI(4,5)P2 binding region of avian sarcoma virus Gag, the chimeric Gag localized to the PM but did not release VLPs efficiently (73). The order of Gag-PM binding and multimerization into Gag puncta varies between different retroviruses (74,75), suggesting that membrane binding and multimerization need to be coordinated for optimal particle assembly. Thus, it is conceivable that the release defect of 29/31KR GagLZ-YFP may be due in part to a change in Gag multimerization caused by the absence of the native NC domain or the presence of the LZ motif or YFP tag that becomes apparent in the context of the 29/31KR mutation.…”
Section: Discussionsupporting
confidence: 88%
“…Analogous to our observation, a recent study found that when the MA domain of HIV-1 Gag was replaced with the N-terminal PI(4,5)P2 binding region of avian sarcoma virus Gag, the chimeric Gag localized to the PM but did not release VLPs efficiently (73). The order of Gag-PM binding and multimerization into Gag puncta varies between different retroviruses (74,75), suggesting that membrane binding and multimerization need to be coordinated for optimal particle assembly. Thus, it is conceivable that the release defect of 29/31KR GagLZ-YFP may be due in part to a change in Gag multimerization caused by the absence of the native NC domain or the presence of the LZ motif or YFP tag that becomes apparent in the context of the 29/31KR mutation.…”
Section: Discussionsupporting
confidence: 88%
“…Analogous to our observation, a recent study found that when the MA domain of HIV-1 Gag was replaced with the N-terminal PI(4,5)P2 binding region of avian sarcoma virus Gag, the chimeric Gag localized to the PM but did not release VLP efficiently (67). The order of Gag-PM binding and multimerization into Gag puncta varies between different retroviruses (68). The majority of HIV-1 Gag is directly recruited to Gag puncta at the PM from the cytosol rather than after binding elsewhere on the PM (68, 69).…”
Section: Discussionmentioning
confidence: 99%
“…The order of Gag-PM binding and multimerization into Gag puncta varies between different retroviruses (68). The majority of HIV-1 Gag is directly recruited to Gag puncta at the PM from the cytosol rather than after binding elsewhere on the PM (68, 69). Thus, it is possible that a change in this order due to the LZ substitution of NC may have made a step in VLP assembly, such as membrane curvature, more dependent on the native sequence of MA-HBR.…”
Section: Discussionmentioning
confidence: 99%
“…HIV assembly was observed on the plasma membrane of live cells using TIRF microscopy, both through tagging the HIV Gag at its C-terminus with GFP and observing the assembly dynamics by monitoring formation of virus like particles [ 21 ] or tracking the assembly of virions with GFP inserted in between the MA and CA domains of Gag [ 22 , 23 ], both of which reported stochastic spontaneous nucleation of Gag on the plasma membrane followed by assembly of virions through addition of Gag molecules following a sigmoidal curve lasting 5–10 min. Using TIRF microscopy as well as photo-switching it was also possible to confirm that new HIV Gag molecules arrive at the assembly site through cytosol while human T-lymphotropic virus (HTLV) Gag assembles by recruiting additional Gag molecules from the adjacent plasma membrane [ 24 ]. The evanescent filed generated in TIRF mode can be well calibrated and used as a tool to measure the distance molecules travel away/towards the glass/media interface, this aspect of the TIRF microscopy was significantly developed during study of endocytosis [ 25 , 26 ] and applied to study the assembly of HIV demonstrating the coupling of curvature creation and Gag polymerization during HIV assembly [ 27 ].…”
Section: Total Internal Reflection Fluorescence (Tirf) Microscopy mentioning
confidence: 99%